Biliary metastasis in colorectal cancer confers a poor prognosis: case study of 5 consecutive patients - Koh FH ([Seoul, Korea] : Korean Association of Hepato-Biliary-Pancreatic Surgery, [2016]- Copyright Date: 2016-, 2018)
10.14701/ahbps.2017.21.1.57.